IbM kelompok usaha ikan salai lele dan kerupuk ikan - Mery Sukmiwati; N Ira Sari; Dahlia Dahlia (Unri Conference Series: Community Engagement, 2019)
Counselling and training at the business group of smoked fish and fish cracker were aimed to understanding how to produce good food for home industries is an important factor for quality standards useful for the continuation of the food industry, Through this CPPB the food industry can produce quality food, suitable for consumption and safe for health. There are 3 methods of the approach taken, namely: extension methods include CPPB to improve food security, food quality and product shelf life. Training methods include: making smoked fish products and fish crackers, accompaniment methods: managing business and production permits to the Health Office. The results of counselling and training that the problem of the chimney has been renovated so that the smoke appears when burning has been thrown out of the room. CPPB-IRT counselling and integrated micro-entrepreneurship management have been carried out for both partners. It has been carried out counselling on handling, processing fresh fish, storing fish and assisting in making cracker packaging and labelling designs. Assist in obtaining P-IRT permit from the Health Office. Targets to be achieved on smoked fish products and fish crackers must meet smoked fish (SNI 1992) and (SNI 1999) fish crackers.